The Role of the legume in the nitrogen cycle of productive and sustainable pastures - Thomas, Richard J. (Wiley, 1992)
The role of the legume in the nitrogen (N) cycle was examined in grazed pastures receiving no N fertilizer of both temperate and tropical regions by simulating the fluxes of N through different processes of the cycle. The amounts of legume‐fixed N required to balance the cycle without invoking a drain on soil organic N reserves (i.e. no net N mineralization) was estimated to vary from 38 to 53% of the above‐ground herbage N or from 20 to 31% on a dry matter (DM) basis for tropical pasture systems with a range of pasture utilization of 10–40%. At higher pasture utilization levels of 50‐70%, more typical of intensively grazed temperate pastures, the N input requirement in the absence of fertilizer N would be 57‐67% of the aboveground herbage N or 35‐45% DM. An examination of the role of each contributory process of recycling (viz. excreta returns, internal cycling or remobilization from senescing tissues, litter decomposition) suggests that variations in the amounts of internally cycled N would have the greatest impact on the requirement for biologically fixed N at low levels of pasture utilization (10‐40%), while at high pasture utilization levels of 70%, variations in the recovery of excreta‐N would have a major effect on the requirement for fixed‐N to balance the cycle.